Morphological study of musculi pectinati and crista terminalis with its applied significance in the human adult cadaver - Ravi Keshri; Rajiv Ranjan (Wolters Kluwer Medknow Publications, 2023)
Background: Morphological studies have highlighted the roles of the crista terminalis (CT) and musculi pectinati (MP) in the process behind cardiac arrhythmias. It is also intriguing to explore the notion that structural problems with the CT and MP may be the major anomaly in those who have atrial flutter and may also account for the incidence of atrial flutter even in people with atria that appear to be normal. The aim is to study the cumulative arrangement and morphology of CT and MP in the right atrium of formalin-fixed human cadavers. Methodology: Cross-sectional descriptive research was conducted on thirty hearts obtained from formalin-embalmed adult human cadavers of the age range between 25 and 65 years (22 males and 8 females). Anatomical course, arrangements, and variations of CT and MP were observed and noted. Results: After meticulous dissection of formalin-fixed human heart, variations associated with the morphological traits of the MP and taenia sagittalis (TS) were observed and recorded. According to the gross anatomical architecture of CT and associated MP, it was classified into six various patterns. Type 1 (MP oriented nearly 90° to CT) was found to be the most common variant, exhibited by 16 (53%) hearts, Type 2 (MP oriented parallel to CT) was noted in 1 (4%), 7 (22%) shown Type 3 (combination of Type 1 and Type 2), Type 4 (branching of the MP) was noted in 2 (7%), Type 5 (interlacing trabeculation) was seen in 3 (10%), whereas Type 6 (prominent muscular column of MP) was present in 1 (4%) of the heart. In addition, the observation on TS (prominent band of MP, seen emerging from CT) was also classified into three groups - Type A (TS was absent) was noted in 15 (50%) hearts was the most common variant, Type B (single trunk of TS) was present in 3 (10%) and Type C (multiple trunks of TS) in 12 (40%) hearts. Conclusion: Cardiovascular catheterization frequently results in injury to Type 6 MP and Type B/Type C TS, which have a more intricate arrangement of fibers. Henceforth, collectively the incidence of these clinically relevant variants was a little more than 50%.